Rambu Solo Traditional Ceremony of The Tana Toraja Tribe: A Sharia Accounting Perspective - Saiful Muchlis; Rimi Gusliana Mais (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The objective of this study is to ascertain the customary ceremonial march and religious observances of Rambu Solos conducted by the Christian community of the Tanah Toraja ethnic group. This research method employs a qualitative approach that deviates from the norm, utilizing a critical paradigm. The critical paradigm aims to effect a comprehensive transformation of societal behaviors that may contradict cultural values, ethics, customs, religion, and other norms. This study's data-gathering methodology involved interviews with three research informants. The researcher used verse 282 from the Al-Qur'an Al-Baqarah to critique livestock loan transactions during the ceremonial event of Rambu Solo. The study findings indicate that the Rambu Solo ritual is a traditional ceremony involving the placement of a long-preserved corpse into a stone burial. The Rambu Solo rite involves exchanging goods or services to settle a debt. The cultural ritual traditions of Rambu Solos events involve using livestock, specifically bonga buffalo and pigs, as a barter system to pay debts. The execution of accounts payable in the traditional Rambu Solo ritual event resembles the implementation of arisan.